Drug-drug interactions affecting drug levels of direct oral anticoagulants in the real world: A systematic review (2020)
Background: Direct oral anticoagulants (DOACs) have emerged as safe and effective alternatives to Vitamin-K antagonists for treatment and prevention of arterial and venous thrombosis. Due to their novelty, pharmacokinetic DOAC drug-drug interactions (DDIs) that result in clinical adverse events have not been well-documented. Objective: This study aims to systematically review reported pharmacokinetic DDIs resulting in clinical adverse events through documented observational evidence to better inform clinicians in clinical practice. Methods: A comprehensive literature review of EMBASE, MEDLINE, and Ovid HealthStar was conducted through March 10th, 2020. Two independent reviewers screened and extracted data from eligible articles according to pre-established inclusion and exclusion criteria. Articles reporting bleeding or thrombotic outcomes in noncontrolled (observational) settings resulting from suggested pharmacokinetic DOAC DDIs were included. Results: A total of 5,567 citations were reviewed, of which 24 were included following data extraction. The majority were case reports (n=21) documenting a single adverse event resulting from a suspected DOAC DDI, while the remaining papers were a case series (n=1) and cohort studies (n=2). The most commonly reported interacting drugs were amiodarone and ritonavir (bleeding), and phenobarbital, phenytoin, and carbamazepine (thrombosis). Bleeding events more often resulted from a combined mechanism (P-glycoprotein AND CYP3A4 inhibition), whereas thrombotic events resulted from either combined OR single P-glycoprotein/CYP3A4 induction.Conclusion: Current literature evaluating the real-world risk of DOAC DDIs is limited to few case reports and retrospective observational analyses. Clinicians are encouraged to continue to report suspected drug interactions resulting in adverse events.